Generation of 2 iPSC clones from a patient with DNAJC12 deficiency: DHMCi003-A and DHMCi003-B - Jung-Klawitter, Sabine; Opladen, Thomas (Stem cell research, 2019)
Skin fibroblasts were isolated from a male patient with DNAJC12 deficiency and reprogrammed to iPSCs using the Cytotune®-iPS 2.0 Sendai Reprogramming Kit (Invitrogen). Two clones, DHMCi003-A and DHMCi003-B, were characterized for expression of pluripotency marker genes (Oct4, Nanog, Lin28, SSEA-4, TRA-1-60) and differentiated into all three germ layers using embryoid body (EB) formation. Karyotype of both clones was normal and presence of the homozygous mutation in the DNAJC12 gene was verified by PCR and Sanger sequencing. Both clones represent a useful tool to study the pathomechanisms underlying the deficiency.
Gesehen am 10.04.2019